Effect of Ethephon Application on Seed Yield and Yield Components of Two Faba Bean (Vicia faba L.) Cultivars - Aybegün Ton (Turkish Journal of Agriculture: Food Science and Technology)
The aim of present study was to determine the effects of different ethephon doses on grain yield and yield components of two faba bean cultivars. The experiment was established in 2019/2020 and 2020/2021 cropping season at Research Area of Field Crops Department, Agriculture of Faculty, Cukurova University Adana, Turkey. The field experiment was laid out in randomized complete blocks design (RCBD) with three replications on the basis split plot design with cultivars (Luz de Otono and Histal) in main plots and ethephon doses (0, 500, 1000, 1500 g ha-1) in sub plots. Plant height (cm), branches per plant, pods per plant, seeds per plant, seed yield per plant (g), 100 grain weight (g), seed yield (kg ha-1) were investigated. Differences among the cultivars and ethephon applications were significant for seed yield and it varied from 1782 to 3388 kg ha-1 in the mean of the years. Seed yield also decreased with increasing ethephon doses. Seed yield was higher in 2019/2020 (3355 kg ha) than 2020/2021 (1841 kg ha-1) where low rainfed and high temperature. The present results suggested that ethephon applications at inititation of flowering were not useful for seed production of faba bean.